Determination Program Priority by Applying Variance Analysis Method in Controlling Electricity Main Supply Cost - Danang Mustika Widya; Bambang Syairudin (IPTEK Journal of Proceedings Series, 2020)
PT. ABC is a State-Owned company managing the electricity sector to meet the needs of the community in providing electricity in Indonesia. Electricity is a commodity that effects the lives of many people, so the basic electricity tariff (TDL) to the community is determined by the government. On the other hand, PT ABC's electricity main supply cost (BPP), are the responsibility of PT ABC itself. The achievement of PT ABC's profits is largely determined by how the BPP is managed and controlled. As of March, the BPP target of the PT ABC power plant managed by PT XYZ was not achieved with an increase in deviation of 27.47 Rp/kWh. The causes of and solutions to the increase in BPP could not be known immediately because PT XYZ did not yet have an analytical method that could explain the causes and their proportions to the increasing deviation comprehensively. Therefore, this study is conducted using the Variance Analysis method in the selection process. The result of this study is the development of BPP controlling method by identifying the BPP component deviations from the predetermined standard costs and suggesting better decision making in prioritizing the work program.